FLACC 08. - FLACC, Genk (Genk : FLACC-Werkplaats voor beeldende kunstenaars, 2008)
Kent Mark ; Maljkovic, David ; Zamora, Hector ; Blondeel, Maria ; Vansant, Tom ; et al.
Box met aparte kleine boekjes.
Overzicht werkjaar 2008 in FLACC, Genk.
kunstcatalogus